Apparent diffusion coefficient as a potential marker for tumour differentiation, staging and long-term clinical outcomes in gallbladder cancer - Min, Ji Hye; Kang, Tae Wook; Cha, Dong Ik; Kim, Seong Hyun; Shin, Kyung Sook; Lee, Jeong Eun; Jang, Kee Taek; Ahn, Soo Hyun (European Radiology, 2019)
Objectives: To evaluate the correlation between tumour differentiation or stage of gallbladder cancer (GBC) and the apparent diffusion coefficient (ADC), as well as to assess whether ADC value can predict long-term disease-free survival (DFS) after surgery. Methods: This retrospective study was approved by the institutional review board and the requirement for informed consent was waived. Between March 2008 and June 2016, 79 patients who underwent magnetic resonance (MR) imaging with diffusion-weighted image and subsequent surgery for GBC were included in this study. Correlations between quantitative ADC values and tumour differentiation or stage based on the American Joint Committee on Cancer (AJCC) were assessed using Spearman’s correlation analysis. Prognostic factors for DFS were identified with multivariate Cox regression analysis using imaging and clinical characteristics. Results: All patients were classified as having well- (n = 18), moderately (n = 35) or poorly differentiated GBCs (n = 26). The ADC value of GBCs was significantly correlated with tumour differentiation and AJCC stage (p < 0.001 and p < 0.001, respectively). Sixty-nine patients were followed up for 2.0–92.4 months (median, 23.5 months). On multivariate analysis, the significant prognostic factor for DFS was not tumour differentiation or AJCC stage but a binary tumour ADC value (hazard ratio, 4.29; p = 0.009). DFS rates were significantly different according to the classification of tumour ADC value (cut-off value = 1.04 × 10−3 mm2/s; p = 0.004). Conclusion: The ADC value of GBCs was significantly correlated with tumour differentiation as well as AJCC stage. In addition, it predicted long-term outcomes after surgery in patients with GBC. Key points: • ADC values of GBC and tumour differentiation were negatively correlated. • Lower ADC values of GBC were significantly correlated with higher tumour stage. • Tumour ADC value could be useful for risk stratification of GBC patients.
Keywords: Adult; Aged; Aged, 80 and over; Diffusion Magnetic Resonance Imaging; Disease-Free Survival; Female; Follow-Up Studies; Gallbladder Neoplasms; Humans; Male; Middle Aged; Neoplasm Staging; Prognosis; Retrospective Studies; Time Factors; Diffusion; Gallbladder neoplasms; Magnetic resonance imaging; Treatment outcome